Optimal Non-Linear Income Taxation for the Alleviation of Income Poverty - Ravi Kanbur; Michael Keen; Matti Tuomala (Queen's University, Department of Economics, 1990)
This paper is concerned with the optimal use of income information in the design of tax/transfer systems to alleviate poverty. The issue is one of optimal non-linear income taxation, but using a non-welfarist objective function that seems to accord well with the common concerns of policy debate: an income-based poverty index. We show that one of the key results of the welfarist literature is overturned: if it is desirable for everybody to work, the optimal marginal tax rate on the very poorest individuals is strictly negative. More generally, it is argued that the non-welfarist perspective points towards lower marginal tax rates in the lower part of the distribution than does the welfarist. Numerical simulations suggest, however, that this effect is of limited quantitative significance. Using conventional functional forms and parameter values, optimal marginal tax rates on the poor are in the 60-70% range.
Keywords: 330